INVASIVE PLANT SPECIES IN THE DISTURBED FOREST OF BATUKAHU NATURE RESERVE, BALI, INDONESIA - Laily Mukaromah; Muhammad Ali Imron (BIOTROPIA, 2020)
Patterns of invasive plant distribution and their underlying mechanisms are complex and vary with spatial scale. Within the mountainous tropical ecosystems of Bali Island, local-scale patterns of invasive plants are still poorly understood. This paper aimed to detect and investigate the presence of invasive species and to evaluate their relative abundance linked to forest site conditions along an elevation range on Mount Pohen, Batukahu Nature Reserve, Bali, Indonesia. To identify the importance of environmental disturbances on species invasion, disturbance-environmental factors and species-environmental relationships were also measured and examined. Using a stratified random sampling approach, 78 vegetation plots of 2 × 2 m size were established across four forest sites. Ten invasive plant species belonging to ten genera and five families were identified. Of these invasive species, 40% were herbs, while shrubs and grasses each comprised 30%. Austroeupatorium inulaefolium had the highest frequency (45% of plots), followed by Ageratina tipatia and Brachychaeta reptans (40% of plots each), Melastoma malabathricum (37%), and Calliandra calothyrsus (27%). Austroeupatorium inulaefolium was the most abundant invader, followed by Ageratina tipatia, and the remaining invasive species were Pennisetum purpureum, Calliandra calothyrsus, Imperata cylindrica, Brachychaeta reptans, Melastoma malabathricum, Lantana camara, Bidens pilosa, and Blumea lacera. The distribution of invasive plants was strongly linked to the disturbance level of their respective habitats. The largest numbers of invasive plants were present in burnt sites close to forest edges with direct anthropogenic influence, while the undisturbed forest was the least invaded site. Furthermore, most invasive species mainly occurred at low elevations up to 1,600 m a.s.l. and were rarely found at higher elevations. However, a few invasive species, such as Austroeupatorium inulaefolium and Melastoma malabathricum, were able to colonize the highest altitude (2,035 m a.s.l.), and, to a lesser degree, Ageratina tipatia and Brachychaeta reptans were also distributed at high altitudes (1,950 m a.s.l. and 1,972 m a.s.l., respectively). This study provides a fine-scale analysis of invasive species distribution, which will serve as a basis for conservation purposes, especially for strategic planning regarding the detection and management of invasive alien plants.